PEMBELAJARAN SAINS BERMUATAN KARAKTER ILMIAH DENGAN ALAT PERAGA BARANG BEKAS DAN ASESMEN KINERJA - Kurniawati, Wahyu; Atmojo, Setyo Eko (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The purpose of this study is to develop the scientific character of science learning laden with props thrift and performance assessment. This type of research is research and development. The technique of collecting data using questionnaires, observation and tests. Data were analyzed using descriptive analysis percentage. The results showed that the validity of the learning pernagkat validity of the development value (Va) 4.23 which is the valid criterion (4 â¤ Va <5). Scientific character within students in science learning laden scientific character with props used items that are in good category where the average percentage of scientific character on each Class of> 70%. The average percentage of student activity is in the good category that is> 70%. Cognitive abilities of students in the class A1 of 84.44% cognitive ability and very good 13.33% of the students in the category fairly and 2.22% of students are in the poor category. In the A2 grade of 80.43% of the students have the cognitive ability and very good and the rest have the cognitive abilities in the category enough. In the A3 grade of 89.13% of the students have the cognitive ability and very good as well as the A4 grade of 93.33% of the students have the cognitive ability and very good san rest have sufficient cognitive ability.